Computational modeling of nanosecond time-scale charge carrier dynamics in organic semiconductors. Issue 1737 (20th May 2015) - Johnson, Brian; Paudel, Keshab; Ostroverkhova, Oksana
ABSTRACT: We present a study of photoinduced charge carrier dynamics in single crystals and polycrystalline thin films of a functionalized fluorinated anthradithiophene (ADT) derivative, ADT-TES-F, combining measurements of time-resolved photocurrent with computational modeling. Simulations revealed two competing charge generation pathways: ultrafast charge separation and nanosecond (ns) time-scale exciton dissociation. Single crystals exhibited significantly enhanced fast charge photogeneration and charge carrier mobilities, as well as lower charge trap densities and free hole-trapped electron recombination, as compared to thin films. At sub-ns time scales after photoexcitation, the light intensity dependence of the photocurrents obtained in single crystals was determined by the carrier density-dependent recombination. At longer time scales, and at lower intensities, taking into account carrier concentration-dependent mobility improved agreement between numerically simulated and experimentally measured photocurrent data.